137 Audiologic monitoring of cisplatin ototoxicity in cancer treatment of adults: a balance between overdiagnosis and patient safety?. (20th August 2018) - Rhainds, Marc; Bussières, Martin; L'Espérance, Sylvain; Nourissat, Alice; Coulombe, Martin
Abstract : Objectives: Cisplatin, despite its effectiveness against various malignancies, can lead to serious side effects such as ototoxicity. However, ototoxicity monitoring has been shown inconsistent during drug treatment for adults. Over the last few years, a protocol on systematic audiologic monitoring for ototoxicity in adults receiving chemotherapeutic treatments has been developed by the audiology department of our hospital. Due to limited resources to manage a high volume of patients, the audiology department was unable to fully implement the protocol. The main objective of this project was to evaluate the most suitable approach to manage audiologic monitoring in adults receiving cisplatin. Method: Literature searches were conducted in several databases and grey literature to retrieve data on audiologic monitoring and cisplatin ototoxicity in adults including systematic reviews, guidelines and primary studies. Two review authors (MB and SL) independently performed document selection, methodological quality assessment and data extraction. A web-based survey was carried out in 2017 to document the clinical practice of audiologists in Québec for cisplatin ototoxicity management. A local survey in our institution was also performed to describe roles and involvement of pharmacists, hematologist-oncologists and specialized oncology nurses relative to cisplatin ototoxicity monitoring. Data extraction from Electronic Patient Record (EPR) were performed to review local practice regarding cisplatin ototoxicity monitoring in 125 adults treated from 2015 to 2017. Evidence-based review and local perspective were shared with an interdisciplinary group including oncologists, audiologists, pharmacists, oncology nurses and hospital managers. Results: Six publications specific to cisplatin ototoxicity monitoring in adults were retrieved. Clinical practice guidelines suggested that an audiologic monitoring program should be available for all patients including repeated audiologic tests. Results from literature and Quebec web-based survey showed that audiologic monitoring programs are often unknown and not always enforced in clinical practice. In our hospital, data from the EPR suggested that audiologic consultation before starting, during or after stopping chemotherapeutic treatments was performed in 35 patients (28%), mainly for head and neck cancer, and high cisplatine dose. Results from the local survey highlighted concerns about the chemotherapy treatment decision making process when ototoxicity is diagnosed and the importance of communication between audiologists, oncologists, pharmacists, nurses and patients. Threshold level to interpret audiologic tests was also among the concerns because of the risk of overestimating patients having nonsignificant hearing loss, and the consequences of less effective anticancer treatment options. Conclusions: Results suggest that audiologic monitoring in adults under cisplatin cannot rely only on audiometric testing by audiologists. An adapted approach based on an interdisciplinary collaboration, patient's individual preferences as well as therapeutic alternatives should be the preferred way to promote share-decision making on cisplatin ototoxicity risks, preventive measures and auditory rehabilitation available.